FUNGSI LAPO TUAK DI DESA SIABU KECAMATAN SALO KABUPATEN KAMPAR - Prasetya, Yuyung Dwi; Bahri, Syamsul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Tuak is also a traditional alcoholic drink originating from the North Sumatra region. One of the villages in Kampar Regency, Salo Subdistrict, namely Siabu Village has a fairly high proportion of tuak drinkers, most of the Siabu Village people have been consuming tuak since they were teenagers. This is due to the strong tradition and habit of drinking tuak in the community. In addition, not all of the villagers are Muslim, but some are Catholic, so there are no restrictions and prohibitions on consuming alcohol. The purpose of this research is to find out who uses lapo tuak, how the socio-economic and cultural functions take place in lapo tuak activities, as well as the government's response to the existence / existence of tuak lapo to the community in Siabu Village, Salo District, Kampar Regency. The method used is descriptive qualitative analysis techniques that describe, explain, or summarize various conditions, situations, social phenomena according to events as they are which can be photographed, interviewed, observed, and which can be expressed through documentary materials. The results of this study indicate that the owners and visitors of lapo tuak are Christian owners and visitors over 30 years of age, and old lapo tuak visitors and some teenagers. The socio-economic and cultural functions of the lapo tuak activity take place, the socio-economic functions are not good, while the cultural functions take place very well. The government's response to the existence of lapo tuak is the stipulation of the Kampar Regency regional regulation Number 8 of 2010 Article 1 concerning the prevention of community diseases which prohibits the existence of lapo tuak, but still the owners of lapo tuak do not comply. The value in this study provides an understanding of the existing functions of lapo tuak. in Siabu Village, and the trigger is the existence of lapo within the communnity. Keywords: Function, Socio-Economic, Lapo Tuak, Culture, Siabu.